Application of LiCoO2 Particles Coated with Lithium Ortho-Oxosalt Thin Films to Sulfide-Type All-Solid-State Lithium Batteries. Issue 8 (1st January 2015) - Ito, Yusuke; Sakurai, Yuki; Yubuchi, So; Sakuda, Atsushi; Hayashi, Akitoshi; Tatsumisago, Masahiro
Abstract : Amorphous oxide thin films in the pseudobinary system Li4 SiO4 -Li3 PO4 and Li4 GeO4 -Li3 PO4 were fabricated using pulsed laser deposition (PLD) with a KrF excimer laser. The ionic conductivities of obtained thin films were 10 −8 to 10 −6 S cm −1 at room temperature. Bulk-type all-solid-state batteries using LiCoO2 particles surface-modified with ortho-oxosalt thin films were constructed to assess the influence of oxide coatings on cell performances. Higher ion-conductive oxide thin films studied here are useful for decreasing the interfacial resistance of all-solid-state cells. The interfacial resistance was lowest in the cell using Li3.5 Si0.5 P0.5 O4 coatings as a buffer layer with estimated thickness of ca. 45 nm. We investigated the dependence of interfacial resistance on film thickness for the oxide systems fabricated in this study. Among them, much lower interfacial resistance was achieved in the cells using Li3 PO4 coatings with film thickness of less than 45 nm. All-solid-state cells using Li3 PO4 -coated LiCoO2 charged and discharged without marked capacity-fading during 30 cycles. Larger discharge capacity after cycling tests was achieved in a cell with a smaller interfacial resistance. The cell using Li3 PO4 -coated LiCoO2 operated at a high current density of 6.4 mA cm −2 with a capacity of 54 mAh g −1 .